Preliminary comparative analysis of antibacterial effects of activated and non-activated of expired platelet concentrate by disc diffusion method - Zabidi, Muhammad Azrul; Mohd Yusoff, Narazah; Sheik Abdul Kader, Zainoodin (Indian Association of Pathologists and Microbiologists, 2012)
Background: Platelets release more than 30 cytokines to provide primary hemostatic function. In addition, platelets are also known to release antimicrobial peptides upon activation by thrombin. Materials and Methods: In this study, comparative analysis of antibacterial activity of activated and non-activated expired platelet concentrate was determined against Grampositive and Gram-negative bacteria by Kirby-Bauer disk diffusion method. Thrombin was used to prepare activated platelet concentrate. Gram-positive bacteria tested in this study were S.aureus and S.pyogenes and Gram-negative bacteria were E.coli and K.oxytoca. All the bacteria used in this study were sensitive strains from clinical isolates. Activated and nonactivated platelet showed no zone of inhibition against S.pyogenes and E.coli. Results: Activated platelet showed antibacterial activity against S.aureus and K.oxytoca with the zone of inhibition of 8.3 ± 0.6 mm and 7.7 ± 0.2 mm, respectively. Zone of inhibition observed in non-activated platelet against S.aureus and K.oxytoca were 7.8 ± 0.4 mm and 7.5 ± 0.3 mm, respectively. Conclusions: These findings showed that no significant differences in antibacterial activity produced by activated and non-activated platelet. However, zone of inhibition observed in activated and non-activated platelet indicate the presence of antibacterial property in expired platelet.